Ni‐Rich Layered Cathode Materials by a Mechanochemical Method for High‐Energy Lithium‐Ion Batteries. Issue 46 (8th December 2020) - Tron, Artur; Hong, Meihua; Don Park, Yeong; Kim, Jiyong; Mun, Junyoung
Abstract: Ni‐rich cathode materials are attractive for use in high energy density lithium‐ion batteries due to low Co, high specific capacity and low cost; however, due to the poor cycling stability of materials with high Ni content of over 80 %, their large‐scale application in electric vehicles is limited. Furthermore, for industrial applications, it is important to simplify the synthetic procedures to reduce the manufacturing cost of the cathode material. A mechanochemical method is introduced for a combination of carbonate and hydroxide starting materials with Ni content of over 80, 85, and 90 %. These precursor materials are stable in air and are easy to use for the synthesis of LiNix Coy Mnz O2 materials by solid state reaction. The crystalline structures and surface morphologies of the obtained mixed precursors and LiNix Coy Mnz O2 powders are characterized using X‐ray diffraction analysis and field scanning electron microscopy with energy dispersive X‐Ray spectroscopy. The electrochemical performance is evaluated by repeat charge‐discharge cycling and measurement of the rate capability for various potential ranges from 3.0 to various high cut‐off potentials of 4.2, 4.3 and 4.4 V vs. Li/Li+. The results suggest that the whole process is very simple and similar to that used in the production of commercial LiNix Coy Mnz O2, with no additional equipment needed in the application of this synthesis method for industrial purposes. Abstract : A mechanochemical preparation of Ni‐rich cathode material for high energy density lithium ion batteries is suggested. A Ni‐rich cathode with 80 % Ni by the proposed method exhibited a long cycle life and a high rate capability. The detailed electrochemical mechanism was investigated by surface and crystalline analyses including EIS.